2021
DOI: 10.1002/agj2.20720
|View full text |Cite
|
Sign up to set email alerts
|

Selection of lactic acid bacteria from native grass silage and its effects as inoculant on silage fermentation

Abstract:  This is the first study of lactic acid bacteria isolated from meadow grassland and typical grassland and their silages on the Inner Mongolian Plateau. Lactic acid bacteria could enhance the fermentation quality of Sorghum-sudangrass hybrid. The strain XM2 performed better and is a potential starter culture for Sorghumsudangrass hybrid silage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Compared with the CK and GFJ treatments, the BP17 and PC3 treatments had lower ( P < 0.05) pH values and NH 3 -N contents. This is likely because the LAB could convert WSC into LA, resulting in a decrease in pH and an increase in the LA content ( You et al, 2021 ). However, since LAB activity plays an important role in LA accumulation and pH reduction in the early stages of ensiling ( Davies et al, 1998 ), LAB from different sources have different effects on the silage quality of PM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the CK and GFJ treatments, the BP17 and PC3 treatments had lower ( P < 0.05) pH values and NH 3 -N contents. This is likely because the LAB could convert WSC into LA, resulting in a decrease in pH and an increase in the LA content ( You et al, 2021 ). However, since LAB activity plays an important role in LA accumulation and pH reduction in the early stages of ensiling ( Davies et al, 1998 ), LAB from different sources have different effects on the silage quality of PM.…”
Section: Resultsmentioning
confidence: 99%
“…The YC1 strain could grow normally at temperatures from 5 to 35 • C, while the PC3 and BP17 strains could grow normally at 15-40 • C. This indicates that the YC1 strain is more resistant to low temperature than the PC3 and BP17 strains. The raw material from which YC1 was isolated (P. arundinacea silage) came from the Qinghai-Tibetan Plateau, while the raw materials from which PC3 (pickle) and BP17 (fresh leaves of PM) were isolated came from Chengdu; therefore, this difference in optimal growth temperature could have arisen due to long-term evolution and natural selection on the different environmental temperatures (You et al, 2021). This unique characteristic of the YC1 strain suggests that it may be used as a low-temperaturetolerant LAB inoculant, consistent with the results of Chen et al (2020a), who reported that L. plantarum isolated from naturally fermented silage on the Qinghai Tibetan Plateau could grow normally at 5-30 • C. The YC1 and BP17 strains could grow normally at pH values ranging from 3.0 to 8.0, while the PC3 strain could grow normally at pH 4-8, and all isolated strains could grow normally with NaCl concentrations of 3% (w/v) and 6.8% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…Klebsiella is a harmful microorganism in silage; it destabilizes the forage aerobically and causes infectious diseases, such as mastitis (Zadoks et al, 2011 ). LAB is found in forage crops and silage, many of which isolates had been identified as part of Lactobacillus group (You et al, 2021a ). Cai et al ( 1999 ) found that Lactobacillus is the main microorganism in forage and silage.…”
Section: Discussionmentioning
confidence: 99%
“…The LAB inoculants could rapidly dominate and overcome the complex microbiome in the raw materials and novel strains have been isolated and identified from various materials and silages as new silage inoculants (Carvalho et al, 2021 ). It is difficult to directly produce high-quality native grass silage because of the lower moisture and water-soluble carbohydrate (WSC) contents, and lower LAB population (You et al, 2021a ). A previous study indicated that the LAB could improve the fermentation quality of native grass silage, especially Lactobacillus plantarum (You et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to directly produce high-quality native grass silage because of the lower moisture and water-soluble carbohydrate (WSC) contents, and lower LAB population (You et al, 2021a ). A previous study indicated that the LAB could improve the fermentation quality of native grass silage, especially Lactobacillus plantarum (You et al, 2021a ). Previously reports also have indicated that the homofermentative LAB could accelerate the fermentation process by utilizing the glucose to produce lactic acid (LA) through the Embden–Meyerhof pathway, such as the certain strains Lactobacillus plantarum, Pediococcus acidilactici , and Pediococcus pentosaceus , whereas, the heterofermentative LAB were also widely used for producing a mixture of LA, acetic acid (AA), and ethanol via the phosphoketolase pathway by improving the aerobic stability, such as the certain strains Lactobacillus buchneri (Gallagher et al, 2018 ; Alhaag et al, 2019 ; Cao et al, 2021 ; Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%